Work-life balance among Croatian employees: role time commitment, work-home interference, and well being - Šverko, Branimir; Arambašić, Lidija; Galešić, Mirta (2002)
This study explores whether work-life imbalance due to long working hours exists among employees in Croatia, and examines some of its antecedents and consequences. In studying the consequences, joint affects of the time spent at work and in home roles are considered in a broader conceptual framework which incorporates the concept of work-life interference. A questionnaire assessing individual and contextual variables time spent at work and in home activities, intensity of work-home conflicts. and subjective well-being teas applied via an on-line survey of Internet users (N = 188), and via Personal interviews (N = 3 19), Since the two data sets did not differ significantly they were merged in the final analysis. The results shou, that 75 percent of the respondents work more than 40 hours a week and 30 percent in excess of 48 hours per week. Hours spent at work and in home activities were not significantly related to subjective well-being (defined as low, levels of stress Symptoms and high levels of life satisfaction), thus questioning the common assumption that more hours mean worse well-being. Work-home interference variables, in particular the work-to-home conflict account for a major part of the well-being variance.
Projekt MZOS
ENG